Respon Pengaplikasian Pupuk Kandang Sapi dan Pupuk NPK Terhadap Pertumbuhan dan Hasil Produksi Bawang Merah (Allium ascalonicum L.) di Polibag - Gulo, Daria Depriani; Harahap, Rahmaniah; Jabat, Yelfi Yana Linda (UNIVERSITAS LABUHANBATU, 2024)
Red garlic (Allium ascalonicum L.) is one of the most important holticultural commodities for society, both in terms of its high economic value and its nutrient content. One attempt to boost the growth of onion crops through cultivation techniques is fertilization aimed at increasing soil productivity by supplying plant nutrients. One of the fertilizers used is cattle barracks and NPK fertilizer in the polybag. In increasing the production of red onions need the addition of the element of hares that are ephesien. This study used a factorial random group plan (RAK) consisting of two factors, namely the first factor of cattle cage fertilization as basic fertilizer (K) consists of three dimensions: K0 = 0 g/polibag, K1 = 100 g / polibag and K2 = 200 g / polyibag. The observed parameters are the height of the plant (cm), the number of leaves (leaves), the amount of bulbs per plant, the weight of the bulb per plot. Analysis with ANOVA, continued with DMRT at 5% if there is a real treatment. Average height of red garlic crop gives the highest results on treatment K1 = 100 g/ polibag and P1 = 3 g/polibag is 25.79 (cm). The best treatment on the number of leaves parameter is K0 = 0 g/Polibag, and the best treatment of P1 is 3 g /polibags of 11.44 leaves. Best treatment on parameter number of bulbs per plant is K1= 100 g / polibags and P2 = 5 g / polyibag of 7.17 bulbs. Keywords: red onions, cattle's cage fertilizer, NPK fertiliser